Renal diseases during pregnancy: Critical and current perspectives - Sukhminder Jit Singh Bajwa; Ishwardeep Singh Kwatra; Sukhwinder Kaur Bajwa; Maninder Kaur (Wolters Kluwer Medknow Publications, 2013)
The advancements in medicine have made early detection and management of medical diseases possible especially during the pregnancy. The physiologic alterations of pregnancy have important implications for renal structure and functions, which may possibly lead to diagnostic dilemmas and wrong interpretation of various investigations carried out during the gestational period. Renal diseases are extremely challenging to treat during pregnancy as various drugs can have adverse effect on the pregnancy outcome. In general, these patients may either progress to normal delivery or may have to undergo surgical delivery under anesthesia. Apart from these anticipated challenges, many other renal problems can develop during the pregnancy in patients with normal renal functions such as urinary tract infections, acute kidney injury or renal trauma. Planning of pregnancy in renal diseases is also associated with increased potential risks especially in patients on dialysis as well as in patients who had undergone renal transplantation.